Zoom-Storytelling : an Activity to Reduce Students’ Speaking Anxiety - Rini Rini; Safrina S Noorman; Nia Nafisah (Edusentris, 2020)
Among the four English skills, speaking is the most difficult skill for students. Speaking English is the most worries things for students in this lesson. There are many reasons that make students reluctant to speak English, including afraid of being laughed at by their friends and lack of confidence. Since the implementation of learning from home by the central government due to the outbreak of the Corona virus, students have increasingly never practiced speaking English. It worsens the level of students' anxiety about speaking English. Therefore, this qualitative case study research was created to help reduce students' anxiety in speaking English by using Zoom-Storytelling, especially when they are required to learn from home. FLCAS was used to measure the student's anxiety level. The results showed that Zoom-Storytelling can reduce students' level of anxiety in speaking English. Through this Zoom-Storytelling activity students can still learn face-to-face virtually even though they are not in school.